PENGARUH GOOD CORPORATE GOVERNANCE DAN KARAKTERISTIK PERUSAHAAN TERHADAP NILAI PERUSAHAAN NON-KEUANGAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - ELVI FAUZIA; INDRA ARIFIN DJASHAN (Jurnal Bisnis dan Akuntansi, 2019)
Good corporate governance mechanism is a step to increase company value. This study was conducted with the aim of obtaining empirical evidence whether managerial ownership, independent commissioners, audit committees, firm size, profitability (ROE), institutional ownership and board size are relatedto firm value. Objects in this study are non-financial companies listed on the Indonesia Stock Exchange during the year 2014-2016. The sample are collected using purposive sampling method and there are 89 companies meet those criteria for sample This research uses multiple regression method for data analysis, where the company's value is measured by Tobin's Q. The results show that profitability (ROE) have an influence on firm value, while managerial ownership, independent commissioner, audit committee, firm size, institutional ownership and board size have no effect